2014
DOI: 10.1111/jocn.12727
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of postoperative intermediate care and standard surgical ward care after emergency abdominal surgery: a qualitative sub‐study of the Incare trial

Abstract: Intermediate care may increase patient perceptions of quality and safety of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other studies have also reported that patients felt restricted by surgical drains, tubes, oxygen lines and continuous monitoring of vital signs during hospital admission. 8 , 10 , 36 , 38 40 To reduce these restrictions, easy access to appropriate walking devices (e.g., the high walking frame with wheels) may facilitate independent mobilization owing to decreased pain when mobilized this way and less insecurity secondary to symptoms of fatigue or dizziness. Furthermore, the walking devices are suitable for transporting all the surgical equipment (e.g., epidural, catheter, intravenous infusion, surgical drains, parental nutrition).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also reported that patients felt restricted by surgical drains, tubes, oxygen lines and continuous monitoring of vital signs during hospital admission. 8 , 10 , 36 , 38 40 To reduce these restrictions, easy access to appropriate walking devices (e.g., the high walking frame with wheels) may facilitate independent mobilization owing to decreased pain when mobilized this way and less insecurity secondary to symptoms of fatigue or dizziness. Furthermore, the walking devices are suitable for transporting all the surgical equipment (e.g., epidural, catheter, intravenous infusion, surgical drains, parental nutrition).…”
Section: Discussionmentioning
confidence: 99%
“…Participants not remembering how much they had been out of bed, their lack of motivation toward physical activity and their diminished health-related quality of life after AHA surgery may have also influenced the feasibility of mobilization during hospital admission in the present study. 38 41 Evidence suggests that using activity monitors so that participants can monitor their level of physical activity from minute to minute can increase time out of bed and physical activity. 42 , 43 Such monitors, therefore, may be added to the mobilization program, especially for independent patients, being relevant for motivation and visual feedback on the amount of mobilization in daily practice during hospital admission, after discharge or in an RCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing ratios decrease as the patient recovers and moves through different levels of postoperative care. One study [ 88 ] illustrated patients’ perspectives around step-down from critical care, interviews confirmed that the transition could be difficult, and patients felt insecure due to greater nursing workload and a perception of busier areas with fewer staff. In the UK specialist nursing roles focused on EL have evolved.…”
Section: Implications Of Eras For Emergency Laparotomy For Nursing Pr...mentioning
confidence: 99%